FACTORS AFFECTING STUDENT MOTIVATION DURING ONLINE LEARNING IN ENGLISH SUBJECT AT SMP ADVENT NARIPAN BANDUNG - Nursalam Simbolon; Cynantia Rachmijati (IKIP Siliwangi, 2022)
The Covid-19 virus epidemic has forced the entire learning structure in educational institutions to be shifted to online learning methods, presenting new challenges to Indonesia's education system. Students experience several changes as a result of the stopping of the learning process directly which has an impact on their motivation to learn. One of the most critical criteria for a good learning process is desire to learn English. One of the variables that has a huge effect on students' enthusiasm for learning is their motivation to learn English. As (Makki & Abid, 2017) said that Intrinsic (internal) motivation and Extrinsic (external) motivation are two terms that can be used to describe motivation. The first motivation is from themselves (intrinsic) and the second is motivation from outside (ekstrinsic), such as people outside the student (teachers, friends, family) or the situation and conditions of the student's environment. Self-motivation or intrinsic motivation is very influential in their learning process. Students who are highly motivated and have a great desire to learn will excel in achieving their learning objectives. This research used a qualitative approach using an instrument questionnaire with junior high school students at SMP Advent Naripan Bandung. The researcher gave two groups of important questions about student motivation in this research, namely intrinsic factors and extrinsic factors by using google form to find out which factor is more dominant. From the research results, it is known that student learning motivation is more dominant from within themselves (intrinsic motivation) has a greater role in their learning process because they are aware of their responsibilities and obligations as students, especially in learning English, although extrinsic factors also have a role influence on their students' motivation. Keywords: Covid-19 Pandemic, Online Learning, Learning Motivation